Lyophyllum deqinense (Lyophyllaceae, Agaricales), a new species from southwestern China - Ma, Yuanhao; Liu, Ping; Zhao, Ziyue; Chen, Weimin; Zhao, Yongchang (Phytotaxa, 2023)
Lyophyllum deqinense sp. nov. is described and illustrated from Yunnan Province, China, based on morphological features and molecular (ITS and LSU) data. The species can be distinguished by a greyish brown to light brown pileus and obtuse central umbo of the pileus, inrolled margin, globose to subglobose basidiospores (5.7–7.2 × 5.5–6.8 µm), clavate basidia (24–34 × 7–10 µm), cespitose and gregarious habit in soil. L. pallidofumosum is similar to the new species in pileus and stipe color, and shape and size of the basidia, but it lacks an obtuse central umbo, has smaller spores (4.5–5.6 × 4.3–5.4 µm), and sometimes is solitary or subcespitose. The combination of morphological characteristics and phylogenetic analyses indicates that the species belongs to the L. decastes complex.